Identification of the risk factors for predicting severe acute kidney injury in patients after liver transplantation - Zhou, Ran; Wang, Huan; Yang, Qi; Han, Lin (Frontiers in Physiology, 2025)
BackgroundAcute kidney injury (AKI) is one of the most common complications after liver transplantation (LT). Few studies have focused on the risk factors for severe AKI (KDIGO criteria: stage 3) after LT. The aim of this study was to identify critical determinants associated with the progression to severe AKI in LT patients admitted to the intensive care unit (ICU).MethodsThis retrospective case–control study analyzed data from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) datasets, version 3.1. Patients were categorized into two groups according to the stage of AKI. Patients diagnosed with AKI stage I or II were placed in the mild-AKI group, and the others diagnosed with AKI stage Ⅲ were placed in the severe-AKI group. Risk factors were figured out through the univariate and multivariable logistic regression models between the groups. Restricted cubic spline (RCS) analyses were conducted to determine threshold effects of the identified risk factors on severe AKI.ResultsA total of 251 patients were enrolled. A total of 131 patients were diagnosed with AKI stage I or II (mild-AKI group), whereas 120 patients were diagnosed with AKI stage Ⅲ (severe-AKI group). Multivariable logistic regression analysis revealed that gender (female), total bilirubin, serum creatinine, and Simplified Acute Physiology Score II (SAPS II) were independent risk factors for severe AKI in LT patients. Male patients had a significantly lower risk of severe AKI than female patients (p = 0.023; OR = 0.349; 95% CI: 0.138–0.854). RCS analysis further revealed nonlinear associations with critical inflection points at total bilirubin 12.189 mg/dL, serum creatinine 1.118 mg/dL, and SAPS-II of 42. Beyond these thresholds, each incremental increase in these parameters demonstrated a statistically significant escalation in severe-AKI risk.ConclusionIn our study, we found that gender (female), total bilirubin (≥12.189 mg/dL), creatinine (≥1.118 mg/dL), and SAPS-II (≥42) are the independent risk factors for severe AKI in patients after LT.